Can we produce carbon and climate neutral forest bioenergy?. Issue 2 (25th March 2014) - Repo, Anna; Tuovinen, Juha‐Pekka; Liski, Jari
Abstract Harvesting branches, stumps and unmercantable tops, in addition to stem wood, decreases the carbon input to the soil and consequently reduces the forest carbon stock. We examine the changes in the forest carbon cycle that would compensate for this carbon loss over a rotation period and lead to carbon neutral forest residue bioenergy systems. In addition, we analyse the potential climate impact of these carbon neutral systems. In a boreal forest, the carbon loss was compensated for with a 10% increase in tree growth or a postponing of final felling for 20 years from 90 to 110 years in one forest rotation period. However, these changes in carbon sequestration did not prevent soil carbon loss. To recover soil carbon stock, a 38% increase in tree growth or a 21% decrease in the decomposition rate of the remaining organic matter was needed. All the forest residue bioenergy scenarios studied had a warming impact on climate for at least 62 years. Nevertheless, the increases in the carbon sequestration from forest growth or reduction in the decomposition rate of the remaining organic matter resulted in a 50% smaller warming impact of forest bioenergy use or even a cooling climate impact in the long term. The study shows that carbon neutral forest residue bioenergy systems have warming climate impacts. Minimization of the forest carbon loss improves the climate impact of forest bioenergy.